News from the BIPM laboratories—2019. (13th March 2020) - Stock, Michael; Wielgosz, Robert; Tavella, Patrizia; Judge, Steven; Milton, Martin
Abstract: In order to fulfil its mission to ensure and promote the global comparability of measurements, the BIPM operates laboratories in the fields of physical metrology, time, ionizing radiation and chemistry. These laboratories act as centres for scientific and technical collaboration between Member States providing capabilities for international measurement comparisons on a shared-cost basis. They coordinate international comparisons of national measurement standards agreed to be of the highest priority, and they establish and maintain appropriate reference standards for use as the basis of key international comparisons at the highest level and provide selected calibrations from them. In the following sections, we provide highlights of the work they have undertaken during 2019.